Trends of Humane Literacy in EFL Assessment as an Alternative for Future Learning: A Systematic Review - Shilvy Inayatillah; Nurul Syafika; Siti Drivoka Sulistyaningrum (Universitas Islam Negeri Palopo, 2026)
Traditional EFL assessment prioritises cognitive and linguistic outcomes, neglecting the affective, ethical, and sociocultural dimensions essential to holistic language development. This study examines publication trends and thematic patterns of humane literacy integration in EFL assessment (2013–2023). Following PRISMA guidelines, five databases (Google Scholar, ERIC, Lens.org, Connected Papers, Open Knowledge) were systematically searched; 23 peer-reviewed articles met inclusion criteria and were analyzed through thematic synthesis appraised using the CASP qualitative checklist. Publication peaks in 2018 (n = 7) and 2023 (n = 4) reflect sustained scholarly interest. Thematic synthesis identified five core humane literacy value factors: comprehensive literacy skills integration, cultural and contextual awareness, critical thinking and ethical reasoning, creativity and innovation, and collaboration and communication. Findings propose